Application of big data in petroleum streams - Gohil, Jay; Shah, Manan (Manan Rajiv) (Boca Raton : CRC Press, 2022)
"The book aims to provide a comprehensive dose of knowledge and information pertaining to application or implementation of big data in petroleum industry and its operations (such as exploration, production, refining and finance). The book covers intricate aspects of big data such as 6Vs, benefits, applications, implementation, research work and real-world implementation pertaining to each petroleum associated operations in a concise manner that aids the reader to apprehend the overview of big data's role in the industry. The book resonates with readers who wish to understand the intricate details of working of big data (along-with data science, machine learning and artificial intelligence) in general and how it affects and brings impact onto an entire industry. As the book builds various concepts of big data from scratch to industry level, readers who wish to gain big data associated knowledge of industry level in simple language from the very fundamentals, would find this as a wonderful read"--
Petroleum operations -- Big data's 6Vs -- Benefits of big data -- Applications of big data -- Implementation of big data -- Big data platforms -- AI algorithms -- Research on big data -- Real world implementation of big data -- Traits of companies with superior big data implementation -- Challenges of big data -- Future scope of big data.
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum industry and trade -- Data processing; Big data; COMPUTERS / Data Processing / General; TECHNOLOGY / Petroleum; TECHNOLOGY / General